Study of Noise Level Distribution at Baiturrahman Mosque, Banda Aceh, Indonesia - ., Maswati; Usmawanda, Tjoet Nia; Yusniar, Viza; Yusibani, Elin (Aceh Physics Society, 2015)
The study of noise level distributions have been done in Baiturahman Mosque area. The measurement take place in different places (near the mosque), times and days. The point of the measurement is choosing based on the high appereance level of noise such as market, park and main road at surrounding of the mosque. The result shows that the average highest level is 82,3 dB and the lower is 58,6 dB.